Analisis Pengaruh Manusia Sebagai Individu Dalam Pengembangan Organisasi di SD Negeri 16 Padang Mentinggi - Rendi Heriza Ibra (GLOBAL SCIENTS PUBLISHER, 2025)
In the context of organizational development, understanding the basic assumptions about human beings is the main foundation for building an effective and sustainable work environment. Some assumptions about humans as individuals in organizational development are that humans have a desire to develop and most people are not only potential, but also want to contribute as much as possible to the organization. The purpose of organizational development is to eliminate factors in the organization that hinder development and prevent people from contributing to achieving organizational goals. This study uses a descriptive qualitative research type, namely research aimed at describing the actual situation or condition in the field and comparing it with existing theories. From the findings at SD Negeri 16 Padang Mentinggi, it was found that employees have high enthusiasm in efforts to improve their competence by participating in KKG (teacher working group) activities, in addition to the role of the principal as an agent of change, encouraging in the sense of providing teacher motivation in efforts to develop the organization in schools. but also encountered obstacles, namely the lack of technological facilities that affect organizational development efforts in schools.